Richard Attenborough - Dux, Sally (British film makers., 2013)
Richard Attenborough's film career has stretched across seven decades; surprisingly, Sally Dux's book is the first detailed scholarly analysis of his work as a filmmaker. Concentrating on his work behind the camera, she explores his initial role as a producer, including his partnerships with Bryan Forbes in Beaver Films (1959-64) and with Allied Film Makers (1960-64). As we know, Attenborough went on to direct twelve films, many of which achieved great acclaim, most notably Gandhi, which won eight Academy Awards in 1982. Attenborough is most renowned for his biographical films including Young Winston, Cry Freedom, Chaplin and Shadowlands, which helped to establish the genre within British cinema. Although his work has often attracted controversy, particularly regarding the representation of individuals and historical events, his films are noted for extracting acclaimed performances from unknown actors such as Ben Kingsley (Gandhi), while maintaining his moral and thematic concerns.